“We have to figure it out ourselves”: Transfeminine adolescents’ online sexual experiences and recommendations for supporting their sexual health and wellbeing - Coyne, Claire A.; Wongsomboon, Val; Korpak, Aaron K.; Macapagal, Kathryn (Frontiers in Reproductive Health, 2023)
Abstract The internet plays a significant role in adolescent sexual development. Sexual and gender minority (SGM) adolescents are more likely than their cisgender, heterosexual peers to use online spaces for sexual and romantic purposes, as they may have a smaller pool of potential partners and more concerns about the risks of in-person partner seeking. Among SGM adolescents, gender identity may shape how youth navigate online spaces for sexual purposes but there is limited research focused on transgender and gender diverse (TGD) adolescents’ online partner seeking. Previous research has focused on cisgender gay and bisexual boys’ experiences with sexual networking applications designed for adult men who have sex with men. This perspective article integrates clinical expertise and survey data from transfeminine adolescents (N=21) in the United States reporting their online sexual behavior and experiences. We use qualitative data to describe the sexual health, safety, and wellbeing of transfeminine adolescents and offer suggestions for clinical assessment of online versus offline sexual activity and call for inclusive sexual health resources for transfeminine adolescents.